PENGARUH CYBERBULLYING TERHADAP REPUTASI CAPRES 2024 ANIES BASWEDAN DI MEDIA SOSIAL - Mutiara Syarafina; Intan Putri; Nanda Syukerti (Jurnal Komunikasi dan Budaya, 2024)
Technological advances have an impact on today's society. This very rapid development provides convenience for humans. We can access various kinds of news and information very easily. Cyberbullying is the misuse of technology by someone by sending messages or uploading pictures and videos to someone with the aim of causing that person to be embarrassed, tortured, made fun of, or threaten them. Through his social media account, Anies Baswedan often shares content that is not only related to personal activities or activities when meeting with the public. The content he displays is also packaged in an attractive appearance accompanied by formal quotes. This research method uses quantitative descriptive research methods. From the research results, researchers concluded that the influence of cyberbullying on the reputation of presidential candidate Anies Baswedan had a significant influence, resulting in satisfactory results.